Effect of Apium graveolens Extract Administration on the Pharmacokinetics of Captopril in the Plasma of Rats - Siska Siska; Abdul Mun`im; Anton Bahtiar; Franciscus D. Suyatna (MDPI AG, 2018)
Apium graveolens (celery) is an edible and traditionally medicinal plant that is used worldwide, among others for the treatment of hypertension. Combining celery with antihypertensive drugs can affect the pharmacodynamics and pharmacokinetics of the latter drugs. The aim of the study is to assess the effects of administrating the celery extract on captopril pharmacokinetics. Sprague-Dawley strain rats were divided into two groups (n = 6). Group I was given captopril (10 mg/kg Body Weight (BW)) orally, while Group II was pretreated with celery extract orally (40 mg/kg BW) an hour before administration of captopril. The blood samples were withdrawn at various intervals after drug administration. The captopril concentration was determined using liquid chromatography-mass spectrometry (LC-MS/MS) and from the blood data, the values of Ke, Cmax, Tmax, T1/2, and area under the curve (AUC) were calculated. The results showed that oral administration of the celery extract increased Cmax (38.67%), T1/2 (37.84%), and AUC (58.10%) and decreased Ke (27.45%) of captopril in Group II (celery + captopril) compared with Group I (captopril). In conclusion, celery extract can alter the pharmacokinetic of captopril when given in combination. The combination might be beneficial for the treatment of hypertension, as celery causes an increase in the plasma level of captopril, which can enhance its efficacy.